Does Drinking Coffee and Tea Affect to the Hemoglobine Level on Women of Reproductive Age at Tengger ? – A Preliminary Research - Wartiningsih, Minarni; Brotosudarmo, Tatas Hardo Panintingjati; Fanny Tanzilia, May; Kodrat, David Sukardi; Sugiyatmi, Tri Astuti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Drinking coffee and tea is a habit of the people of Tengger, East Java, Indonesia, including the women. The polyphenol content in coffee and tea, such as caffeine and tannin, is thought to be one of the factors that can inhibit the absorption of iron in the body. Polyphenols can bind to iron ions to produce compounds that are not useful and will be excreted from the body. So the excessive consumption of polyphenols is thought to cause a decrease in hemoglobin levels wichh indicates anemia. This research was conducted using the cross sectional method and processed using the SPSS application. The result showed that 94% of respondents consumed coffee, 96% consumed tea and 93% consumed coffee and tea every day. In general, the result showed that women of childbearing age with a high frequency of drinking coffe or tea without a mixture had a tendency to have relatively lower hemoglobin levels, compared to those who consumed coffee or tea with a mixture. Menawhile, data related to the habit of drinking coffee and tea without mixture shows relatively lower hemoglobin levels, compared to drinking coffee and tea with a mixture.